2013
DOI: 10.1111/ijfs.12156
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of sunflower oil deodorising: balance between oil stability and other quality attributes

Abstract: Summary The effect of deodorising on basic quality attributes of sunflower oil (free fatty acids, colour, oil stability, total tocopherols) was investigated. The results revealed that the levels of all these quality attributes decreased significantly during the deodorising step. The processing parameters of sunflower oil deodorisation were optimised using response surface methodology. The results revealed the effects of process parameters (temperature, time) on free fatty acids (FFA), colour (LCY and LCR), oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
3
14
1
Order By: Relevance
“…In accordance with Suliman, Meng, Li, Jiang, and Liu (2013), bleaching had a clear impact on carotenes of PSO, may be because of the effect of bleaching earth on yellow pigmentation ( b * value). Part of the color pigments are physically adsorbed by bleaching earth, whereas the other components are chemically bound to bleaching clay via covalent or ionic bonds (Taylor, & Ramsay, 2005; Gibon, De Greyt, & Kellens, 2007).…”
Section: Resultssupporting
confidence: 76%
“…In accordance with Suliman, Meng, Li, Jiang, and Liu (2013), bleaching had a clear impact on carotenes of PSO, may be because of the effect of bleaching earth on yellow pigmentation ( b * value). Part of the color pigments are physically adsorbed by bleaching earth, whereas the other components are chemically bound to bleaching clay via covalent or ionic bonds (Taylor, & Ramsay, 2005; Gibon, De Greyt, & Kellens, 2007).…”
Section: Resultssupporting
confidence: 76%
“…In addition, the tocopherols content of crude camellia oil (325.71±16.32 mg/kg) was significantly higher than that of enzymatic degummed camellia oils (Seen in Table 5). The decrease in the total tocopherols level during the degumming process is in agreement with the results obtained by other researchers (Suliman et al 2013), and the declination of tocopherols may be due to the fact that tocopherols are unstable in the presence of air and light for longer contact time. These results indicated that more attention should be paid on the oxidative stability of degummed oils in further application.…”
Section: Oil Quality Analysissupporting
confidence: 92%
“…Samples of 3.0 g were analyzed under a heating block of 110ºC at a constant air flow of 10 L/h. The tocopherols content of the samples was measured by HPLC-UV according to Suliman et al (Suliman et al 2013). All oil samples were performed in triplicate and the mean values and standard deviations were calculated.…”
Section: Phosphorus Content Assay and Determination Of Oil Quality Inmentioning
confidence: 99%
“…Hydrogenation yields total saturation of double bonds, resulting in miserable cold flow properties [23]. Genetic modification approach is tried either to reduce the saturated fatty acid content of the plant seed oils or to reduce the polyunsaturated fatty acid content, as these constituents have a negative impact on the thermo-oxidative stability [23,25]. Genetically modified oils consistently exhibited improved oleic acid content ranging from 84 to 88% during multiple environmental conditions [26,27].…”
Section: Introductionmentioning
confidence: 99%